A recent (2009–2021) perspective on sustainable color and textile coloration using natural plant resources. Issue 10 (October 2022) - Che, Jiangning; Yang, Xu
Abstract: Fast fashion uses an excessive amount of synthetic dyes and chemical reagents in textile production, while a large quantity of fast fashion apparel and clothes go to the landfill, posting environmental safety concerns. Natural dyes not only produce delicate and subdued shades but also have the potential of novel features to achieve active textile substrate with performance properties such as deodorizing, antioxidant, antimicrobial, antifeedant, UV protection, etc. Developing colored textile products with natural colorants in today's market may enhance consumer interest to an even greater extent. Therefore, finding alternative natural degradable dyes has become one of the leading trends in this field. So far, multiple plants and agriculture byproducts have shown promising results in textile dyeing with increasing sustainability and environmental friendliness. There is no doubt in the general acceptance of natural colorants to be utilized as promising substitutes to synthetic dyes for certain categories of textile products, minimizing the negative impact on the health and the ecosystem. With the continuous advancement of natural dyeing research and technology, the dyes will be elaborated even more with finesse, color yield, stability, and colorfastness. This review gives the present status of natural colorants, natural dyeing and color presentation, natural dyeing methods, technique, and performance, mordants and mordanting for natural dyeing, and selection of suitable Agriculture products/byproducts for natural colorants. We hope to provide readers with specific angles on current natural dyeing applications in the textile and apparel industry. Abstract : Plant dyes; Sustainable natural dyeing; Color gamut of natural dyes.